LEVERAGING AI TOOLS FOR ENHANCING PROJECT TEAM DYNAMICS: IMPACT ON SELF-EFFICACY AND STUDENT ENGAGEMENT - Olena Kuzminska; Denys Pohrebniak; Mariia Mazorchuk; Viacheslav Osadchyi (Інформаційні технології і засоби навчання)
The issue of maintaining group dynamics in flexible remote teams is currently in the focal point of attention not only of commercial companies and government agencies as a response to the changing conditions of work organisation, including those associated with the effects of the COVID-19 pandemic, but also of higher education institutions that train future professionals. Since intragroup dynamics is a key factor affecting team performance, this paper is the result of the study conducted as part of the Group Dynamics and Communications course at National University of Life and Environmental Sciences of Ukraine (NULES) to determine the potential of using AI tools as tools to support the group dynamics of self-organised teams during the implementation of educational projects. Based on the results of the free choice of project and team management tools, we categorised three groups among the 56 participants of the experiment according to the use or non-use of AI tools to enhance group dynamics, followed by self-assessment of the effectiveness of the selected tools in increasing their levels of self-efficacy and social engagement. The survey was based on a Likert scale measurement, and non-parametric methods of analysis and statistical hypothesis testing were used to process the results. The self-assessment confirmed that the incorporation of AI tools in the implementation of a team-based learning project did not influence the improvement of students' social engagement and the dynamics of self-efficacy for both effective and ineffective students. The authors identified the positive impact of using AI tools on its development for students with the average level of self-efficacy. We also presented an example of the use of Notion AI for enhancing group dynamics at each stage of team development according to B. Tuckman. The authors suggest that the impact of using AI tools in the process of implementing a group learning project depends more on personal characteristics of team members than on the choice of a specific AI model. Determination of application specifics of individual AI tools in the process of training future specialists in the implementation of various types of educational activities, particularly ethical considerations is recognised as an area for further research.